A conceptual framework for entrepreneurial personality and entrepreneurial potential traits for Technical and Vocational Education and Training (TVET) students in Malaysia / Norffadhillah Rofa and Rohana Ngah - Rofa, Norffadhillah; Ngah, Rohana (Universiti Teknologi MARA, Kedah, 2022)
This concept paper aims to study the determinants of entrepreneurship potential among Technical Vocational Education and Training (TVET) program students. Recent policy has included TVET to focus on entrepreneurship to cultivate and breed more students' entrepreneurs and graduates' entrepreneurs. Nevertheless, this program is not well enough to equip and support students to fit in paid employment careers as competent-skilled workers and job creators. Prior studies found that entrepreneurial potential can be developed through the entrepreneurial personality traits of individuals involved in Entrepreneurship Education. The components of entrepreneurial personality traits proved as the traits that can lead students to develop entrepreneurial potential. This paper aims to contribute to understanding determinants that affect the entrepreneurial potential of TVET students' programs. Many researches focused on entrepreneurial intention rather than potential studies, and it is conducted in non-Malaysia settings. SPSS will be used to analyse the hypothesized relationships in the proposed conceptual framework. It is hoped that the findings of this study will shed light on the existing literature of entrepreneurial potential among TVET students, specifically the entrepreneurial potential studies from an entrepreneurship academia perspective. Therefore, the paper attempts to explore this context in Malaysia's settings.